Scoping review on assessing climate-sensitive health risks - Chalachew Yenew; Gashaw Melkie Bayeh; Asaye Alamneh Gebeyehu; Anley Shiferaw Enawgaw; Zufan Alamrie Asmare; Amare Genetu Ejigu; Tilahun Degu Tsega; Abathun Temesgen; Rahel Mulatie Anteneh; Zeamanuel Anteneh Yigzaw; Getasew Yirdaw; Sintayehu Simie Tsega; et al. (BMC Public Health)
Abstract Background Climate change is making the existing health problems worse and also introducing new health problem and therefore calls for a wider evaluation of climate sensitive global diseases. The review sought to assess and collate quantitative and qualitative evidence on the effects of climate change on global health, more specifically, infectious and respiratory diseases, the impacts of extreme weather events as well as the implications for mental health with the view of establishing appropriate sustainable and resilience public health measures and policies. Methodology A scoping review of observational studies carried out between the years 2000 and 2024, synthesized information on climate-sensitive health outcomes: infectious diseases, severe weather events, and mental illnesses. This analysis was based on data from PubMed, Scopus, Web of Science and Cochrane Library, where appropriate, utilizing meta-extraction and Meta-analysis techniques. Results A total of 3077 studies were screened, and 96 articles were included for quantitative and qualitative analysis, highlighting the significant health risks posed by climate change. Key areas of concern identified include climate-sensitive infectious diseases, respiratory and cardiovascular conditions, food- and water-borne illnesses, and mental health effects. Rising temperatures and variable rainfall patterns increase the incidence of diseases like malaria (up to 50%) and dengue (8–10% per 1 °C rise). Extreme weather events, such as heatwaves and floods, contribute to a 30% rise in respiratory diseases and a 25% increase in cardiovascular conditions. Food- and water-borne illnesses are more prevalent in regions like Africa (30–40%) due to climate change. Additionally, climate change exacerbates mental health issues, leading to conditions like post-traumatic stress disorder (PTSD), anxiety, and depression. Conclusion and recommendations Climate change amplifies global public health risks, worsening diseases and creating new challenges. To address this, enhance machine learning climate sensitive disease surveillance, strengthen climate resilience health infrastructure, and integrate health into climate adaptation and mitigation strategies, promote sustainable agriculture, improve WASH infrastructure, and foster global collaboration.